Kinetic-powered utraviolet flood water purifying system for stranded flood victims - Gupalor, Paolo Miguel A.; Constantino, Nina Elisa B. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2013)
Flood after typhoons or heavy rains is the most common natural disaster in the Philippines. Although this has been an issue since time immemorial as the cause of faulty sewage systems, illegal logging and such, only a few effective pre-disaster provisions has been made for the stranded flood victims. These victims go dehydrated for up to three days with the abundance of non potable floodwater surrounding them. With this, I came up with a water purifying device that would make floodwater potable through the use of ultraviolet radiation treatment. This device is directed to be efficient and low-cost for the Philippine government to provide to households.
Thesis (Bachelor of Fine Arts - Industrial Design)--University of the Philippines Diliman
Bibliography : page 29.
Keywords: Water -- Purification -- Ultraviolet treatment